Epidemiological patterns and healthcare utilization among malaria patients in Sorong City, Papua, Indonesia: A cross-sectional analysis of national surveillance data - Tri Nugraha Susilawati; Herry Susanto; Oanh Kieu Nguyet Pham; Federika Kondororik; Vivian Nanny Lia Dewi; Hamdiah Ahmar; Noviyati Rahardjo Putri; Rogan Lee; Minh Cuong Duong (PLoS ONE, 2026)
Objectives Malaria remains endemic in Indonesia, with high transmission rates observed in the Papua region. Routine surveillance data are essential to inform service delivery and optimize case management. This cross-sectional study examined malaria cases in Sorong City in 2024 reported through Indonesia’s national surveillance system to describe malaria burden across healthcare facilities, diagnostic and treatment practices, and predictors of hospital attendance and hospitalization. Methods All laboratory-confirmed malaria cases were analyzed, including demographics, malaria diagnosis, disease severity, treatment received, and hospitalization data. Descriptive statistics and logistic regression were used to identify determinants of hospital attendance and inpatient admission. Results Among 3,953 malaria cases, most patients were ≥15 years old (65.9%), males (59.4%), Papuan (54.2%), students (36.6%), and living in highly endemic areas (78%). Community health centers reported most cases (61.7%). Microscopy was the primary diagnostic tool (70.1%). Plasmodium vivax was the predominant species (65.5%), and nearly all infections were uncomplicated (99.9%). Notably, nearly 21% of patients received non-standard antimalarial regimens. Predictors of hospital attendance include older age (aOR: 1.02; 95% CI: 1.00–1.02; p = 0.001), non-Papuans ethnicity (aOR: 1.77; 95%CI: 1.51–2.07; p = 0.001), being housewife (aOR: 1.57; 95%CI: 1.02–2.42; p = 0.041) or student (aOR: 1.56; 95%CI: 1.05–2.31; p = 0.029), and living in moderate- (aOR: 2.01; 95%CI: 1.69–2.40; p = 0.001) or low- (aOR: 4.57; 95%CI: 2.01–10.39; p = 0.001) endemicity areas. Children <15 years were more likely to be hospitalized (aOR 1.9; 95% CI 1.18–3.06; p = 0.009). Conclusions Malaria remains a substantial public health burden, dominated by P. vivax , with community health centers serving as primary care providers. Older individuals were more likely to attend hospital, while younger children had a higher likelihood of hospitalization once diagnosed. Strengthening community-based services, promoting early treatment-seeking among children, and ensuring consistent adherence to national treatment guidelines are critical to reducing severe disease and hospital burden.